A meta-analysis of soil salinization effects on nitrogen pools, cycles and fluxes in coastal ecosystems - Minghua Zhou; Butterbach-Bahl, Klaus; Vereecken, H.; Brüggemann, N. (Wiley, 2017)
Salinity intrusion caused by land subsidence resulting from increasing groundwater abstraction, decreasing river sediment loads and increasing sea level because of climate change has caused widespread soil salinization in coastal ecosystems. Soil salinization may greatly alter nitrogen (N) cycling in coastal ecosystems. However, a comprehensive understanding of the effects of soil salinization on ecosystem N pools, cycling processes and fluxes is not available for coastal ecosystems. Therefore, we compiled data from 551 observations from 21 peer‐reviewed papers and conducted a meta‐analysis of experimental soil salinization effects on 19 variables related to N pools, cycling processes and fluxes in coastal ecosystems. Our results showed that the effects of soil salinization varied across different ecosystem types and salinity levels. Soil salinization increased plant N content (18%), soil NH4+ (12%) and soil total N (210%), although it decreased soil NO3− (2%) and soil microbial biomass N (74%). Increasing soil salinity stimulated soil N2O fluxes as well as hydrological NH4+ and NO2− fluxes more than threefold, although it decreased the hydrological dissolved organic nitrogen (DON) flux (59%). Soil salinization also increased the net N mineralization by 70%, although salinization effects were not observed on the net nitrification, denitrification and dissimilatory nitrate reduction to ammonium in this meta‐analysis. Overall, this meta‐analysis improves our understanding of the responses of ecosystem N cycling to soil salinization, identifies knowledge gaps and highlights the urgent need for studies on the effects of soil salinization on coastal agro‐ecosystem and microbial N immobilization. Additional increases in knowledge are critical for designing sustainable adaptation measures to the predicted intrusion of salinity intrusion so that the productivity of coastal agro‐ecosystems can be maintained or improved and the N losses and pollution of the natural environment can be minimized.